2015
DOI: 10.7314/apjcp.2015.16.14.5595
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Impedance Tomography as a Primary Screening Technique for Breast Cancer Detection

Abstract: Electrical impedance tomography (EIT) is a new non-invasive, mobile screening method which does not use ionizing radiation to the human breast. It is based on the theory that cancer cells display altered local dielectric properties, thus demonstrating measurably higher conductivity values. This article reviews the utilisation of EIT in breast cancer detection. It could be used as an adjunct to mammography and ultrasonography for breast cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The application of 3D EIT technology to detect human breast disease has grown in recent years (16,17). The benefits of 3D EIT include speed, low cost, no radiation, and the advantages of 3D visualization, quantitative evaluation, and functional imaging (18). The pathophysiology of breast cancer might be associated with changes in neoplastic cell membrane permeability, which can be revealed through EIT technology (19).…”
Section: Discussionmentioning
confidence: 99%
“…The application of 3D EIT technology to detect human breast disease has grown in recent years (16,17). The benefits of 3D EIT include speed, low cost, no radiation, and the advantages of 3D visualization, quantitative evaluation, and functional imaging (18). The pathophysiology of breast cancer might be associated with changes in neoplastic cell membrane permeability, which can be revealed through EIT technology (19).…”
Section: Discussionmentioning
confidence: 99%
“…An obvious difference in trans‐epithelium potential (TEP) was observed between that of the normal and transformed breast epithelium [Marino et al, 1994]. The electropotential measurements were applied clinically to diagnose the early onset of breast cancer [Cuzick et al, 1998; Akhtari‐Zavare and Latiff, 2015]. Several studies have demonstrated abnormal EF properties around the tumor tissue in vivo [Melczer and Kiss, 1957; Mishra et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…In the past three decades, several research groups have investigated EMI for imaging the electromagnetic properties (EPs, conductivity, permittivity, and permeability) of biological tissues using low-frequency (<10MHz) electromagnetic (EM) spectrum [ 6 , 7 , 8 , 9 ]. EMI has been applied to detect several diseases, including gastric emptying [ 10 ], lung ventilation [ 11 ], breast cancer [ 12 ], prostate cancer [ 13 ], pulmonary perfusion [ 14 ], and acute cerebral stroke [ 15 ]. EMI has been extensively studied for monitoring neurological diseases and injuries, including hemorrhagic stroke [ 16 ], ischemic stroke [ 17 ], and brain edema [ 18 ].…”
Section: Introductionmentioning
confidence: 99%